Cursorial ecomorphology and temporal patterns in theropod dinosaur evolution during the mid-Cretaceous - Kohta Kubo; Yoshitsugu Kobayashi (Royal Society Open Science, 2025)
Coelurosauria, including modern birds, represents a successful group of theropod dinosaurs that established a high taxonomic diversity and significant morphological modifications. In the evolutionary history of this group, a specialized foot morphology, the arctometatarsus, evolved independently in several lineages and has been considered an adaptation for cursoriality. While its functional significance has been extensively studied, the temporal pattern of this parallel evolution, as well as its origin and influencing factors, remains largely unresolved. Here, we show the temporal evolution of cursorial traits, including the arctometatarsus and hind limb proportions. Our study reveals that the proportional elongation of distal hind limb segments preceded the evolution of the arctometatarsus in ornithomimosaurs and oviraptorosaurs. In contrast, in tyrannosauroids, alvarezsaurs and troodontids, the proportional elongation of the tibia and metatarsals occurred in parallel with the acquisition of the arctometatarsus. The evolutionary history of the arctometatarsus further highlights the presence of a phylogenetic constraint outside Coelurosauria, as this foot specialization is restricted to members of this group. Finally, our date estimation, based on compiled evolutionary patterns, demonstrates that these cursorial traits emerged during the mid-Cretaceous (93–120 Ma), suggesting selection on theropod locomotor performance throughout this interval.